Structure of Thiacalix[4]crown-5 Derivative - Zhao, Jiang-Lin; Jiang, Xue-Kai; Mu, Lan; Zeng, Xi (Asian Journal of Chemistry, 2010)
The single crystal of 1,3-alternate-25,27- bis(2-phthalimidoethoxy) thiacalix[4]crown-5 (1) was obtained by recrystallization from its chloroform-methanol (2:1 v/v) solution. Its structure was confirmed by single crystal X-ray analysis. It crystallizes in the triclinic system (space group, P-1) and the chloroform solvent molecular occupies interstitial lattice space between two calixarene molecules. It displays 1,3-alternate conformation. The crystal packing is stabilized by weak C-H···p contacts.